Окремі питання нормативного закріплення мети і завдань кримінального провадження щодо неповнолітніх як засіб відображення його охоронної спрямованості - Романюк, В. В.; Romaniuk, V. V.; Віталій Романюк (Право і безпека. - 2014. - № 1 (52). - С. 114-119, 2014)
Визначено мету та завдання кримінального провадження щодо неповнолітніх, які забезпечують відображення його виховної спрямованості та охоронного типу, запропоновано їх формулювання у нормативному вигляді. Зазначено необхідність їх більш детальної нормативної регламентації, що відповідає міжнародним стандартам прав дитини.

The relevance of the research concerning issues of juveniles’ criminal justice is due to the need for proper implementation of the UN Convention «On Child Rights» and a number of other international and legal acts in this field into the national legislation. And this is the condition of the duties taken by Ukraine. In particular it is related to the realization of the Law of Ukraine «On the General State Program» «National Plan for Realizing the UN Convention on Child Rights» for the period up to 2016» on creating a juvenile justice system in order to improve national legislation in the field of child rights. Therefore, identification of the main features and characteristics of the criminal proceedings concerning minors and processing appropriate proposals to the law is an important task towards guaranteeing realization of the stated National Plan and enhancing minors’ protection in the criminal proceedings. Special attention is paid that the content of the criminal proceedings concerning juveniles is the commission of procedural actions and adoption of procedural decisions in connection with the offense commission by a minor under the law of Ukraine on criminal liability. Proper and specific procedural relations arise in the course of these actions, namely the proceedings are carried out in a certain, inherent way. It is noted that the characteristics of the relevant procedural relations, specifics of realizing this procedure are due to its essential features, which determine its direction and purpose. Thus, attention is paid to the aspect of its nature, which must find its realization and realization while the preliminary investigation and court proceedings. The objective and tasks of the criminal proceedings concerning juveniles are defined. These tasks and objective provide reflection of its educational focus and protective type. Their formulation in a normative way is offered. The need of more detailed of their normative regulations corresponding to international standards of child rights is noted.

Определены цель и задачи уголовного производства в отношении несовершеннолетних, которые обеспечивают отражение его воспитательной направленности и охранного типа, предложены их формулировки в нормативном виде. Отмечена необходимость их более детальной нормативной регламентации, что соответствует международным стандартам прав ребёнка.
Отдельные вопросы нормативного закрепления цели и задач уголовного производства в отношении несовершеннолетних как средство отображения его охранной направленности
Some issues of regulatory consolidation of the objective and tasks of the criminal proceedings concerning juveniles as a mean of displaying its protective orientation
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; неповнолітні; кримінальне провадження щодо неповнолітніх; міжнародні стандарти; права дитини; права неповнолітнього; дитина; criminal proceedings against minors; criminal procedural guarantees; international standards of child rights; juvenile justice; children rights; minors rights; minors; child; ювенальна юстиція; ювенальная юстиция; уголовное производство в отношении несовершеннолетних; уголовно-процессуальные гарантии; международные стандарты прав ребенка; права ребёнка; права несовершеннолетних